Hyperglycaemic progression in subjects with impaired glucose tolerance: association with decline in beta cell function. - Cook, J; Page, R; Levy, J; Hammersley, MS; Walravens, E; Turner, R (1993)
Impaired glucose tolerance is associated with an increased risk of Type 2 diabetes. This prospective cohort study has examined the variables associated with hyperglycaemic progression in order to elucidate the aetiology of this deterioration. The 5 mg glucose.kg ideal body weight.min-1 continuous infusion of glucose with model assessment (CIGMA) test was used to quantitate glucose tolerance, beta cell function, and insulin sensitivity. Twenty-two Caucasian subjects who had impaired glucose tolerance identified on two separate tests underwent repeat testing after a median period of 24 months. At follow-up, 2 of the 22 subjects (9%) had Type 2 diabetes, 18 (82%) had impaired glucose tolerance, and 2 (9%) were normoglycaemic. The fasting and achieved (60-min) glucose levels were significantly higher at follow-up (mean +/- SD) (5.7 +/- 0.8 vs 5.5 +/- 0.5 mmol l-1, p = 0.029 and 10.0 +/- 0.9 vs 9.6 +/- 0.6 mmol l-1, p = 0.021, respectively), and beta cell function was significantly lower (median and interquartile range): 75% (50-93%) vs 90% (70-135%), p = 0.009. The changes in fasting plasma glucose were found to correlate with change in body mass index (rs = 0.46, p = 0.03). We conclude that impaired glucose tolerance is associated with decline in beta cell function, and denotes substantial risk of hyperglycaemic progression. Randomized controlled trials are warranted to determine whether exercise programmes, dietary advice, and attentive follow-up and effective preventive strategies for subjects with impaired glucose tolerance.